PENGARUH STRATEGI PEMASARAN TERHADAP MINAT BELI KONSUMEN PADA CALYSTA SKIN CARE CLINIC KOTA SUKABUMI - Mia Indriani; Deri Firmansyah (Journal of Business Education and Social, 2020)
The world of beauty is currently developing quite rapidly. Awareness of an appearance is considered very important, both for women and the adam as supporting the appearance. An interesting phenomenon in this study is that Calysta Skin Care Clinic for the past few years has been in the second position in mastering market share among some of the closest clinics in Sukabumi City. The purpose of this study was to determine the effect of marketing strategies on consumer buying interest in Calysta Skin Care Clinic in Sukabumi City.The design in this study uses a survey method with a descriptive approach and associative methods. The population in this study were all consumers of Calysta Skin Care Clinic in Sukabumi City, the samples used were consumers who came to the Clinic in 2018 using the Slovin formula approach. For statistical analysis and relationship analysis used Pearson product moment correlation, coefficient of determination, simple linear regression and to test the hypothesis used t test.Based on the results of research that has been done it can be seen that the marketing strategy has a very positive effect on consumer buying interest. By comparing tcount with ttable (6.682 < 1.986), it means that H0 is rejected and H1 is accepted, so the research hypothesis proposed in this study is proven that the marketing strategy influences consumer buying interest. The magnitude of the contribution of the influence of marketing strategies on consumer buying interest is 32.7%, while the remaining 67.3% is influenced by variables not examined outside of marketing strategies including customer perception, service quality and store atmosphere. It is expected that the next research needs to consider other factors, not only limited to marketing strategies, because there are other possible variables that have more significant influence on buying interest in the consumer.